Improvements in meta-heuristic algorithms for minimum cost design of reinforced concrete rectangular sections under compression and biaxial bending. (1st January 2017) - Sánchez-Olivares, G.; Tomás, A.
Highlights: A numerical procedure for minimum cost design of RC rectangular sections is proposed. Cross sections are loaded under compression and biaxial bending. A new fitness function which does not use penalty coefficients is proposed. The procedure has been simplified as far as possible to reduce the computational cost. The procedure is capable of obtaining designs near to the global optimum. Abstract: A numerical procedure is proposed in this paper for achieving the minimum cost design of reinforced concrete rectangular sections under compression and biaxial bending by using biologically-inspired meta-heuristic optimization algorithms. The problem formulation includes the costs of concrete, reinforcement and formwork, obtaining the detailed optimum design in which the section dimensions and the reinforcement correspond to values used in practice. The formulation has been simplified in order to reduce the computational cost while ensuring the rigor necessary to achieve safe designs. The numerical procedure includes the possibility of using high-strength concrete and several design constraints, such as minimum reinforcement and limiting the neutral axis depth. Two numerical examples are presented, drawing comparisons between the results obtained by ACI318 and EC2 standards.